7‐Dehydrocholesterol Encapsulated Polymeric Nanoparticles As a Radiation‐Responsive Sensitizer for Enhancing Radiation Therapy. Issue 17 (18th March 2022) - Delahunty, Ian; Li, Jianwen; Jiang, Wen; Lee, Chaebin; Yang, Xueyuan; Kumar, Anil; Liu, Zhi; Zhang, Weizhong; Xie, Jin
Abstract: Therapeutics that can be activated by radiation in situ to enhance the efficacy of radiotherapy are highly desirable. Herein, 7‐Dehydrocholesterol (7‐DHC), a biosynthetic precursor of cholesterol, as a radiosensitizer, exploiting its ability to propagate the free radical chain reaction is explored. The studies show that 7‐DHC can react with radiation‐induced reactive oxygen species and in turn promote lipid peroxidation, double‐strand breaks, and mitochondrial damage in cancer cells. For efficient delivery, 7‐DHC is encapsulated into poly(lactic‐ co ‐glycolic acid) nanoparticles, forming 7‐DHC@PLGA NPs. When tested in CT26 tumor bearing mice, 7‐DHC@PLGA NPs significantly enhanced the efficacy of radiotherapy, causing complete tumor eradication in 30% of the treated animals. After treatment, 7‐DHC is converted to cholesterol, causing no detectable side effects or hypercalcemia. 7‐DHC@PLGA NPs represent a radiation‐responsive sensitizer with great potential in clinical translation. Abstract : 7‐Dehydrocholesterol (7‐DHC)‐loaded PLGA nanoparticles are a promising radiosensitizer. 7‐DHC reacts with radiation‐induced radicals, in turn propagating radical chain reactions among polyunsaturated fatty acids. This leads to lipid peroxidation and mitochondrial damage, enhancing the efficacy of radiation therapy. After treatment, 7‐DHC is metabolized to cholesterol, causing minimum side effects to the host.